Edukasi tentang Senam Ibu Hamil di Wilayah Puskesmas Perumus dalam Kota Banjarmasin Tahun 2023 - Prihatanti, Nur Rohmah; Isnaniah, Isnaniah; Yuliastuti, Erni; Maslani, Noorhayati (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Pregnancy exercise is a fitness program for pregnant women. Therefore, pregnancy exercise has special movement principles that are adapted to the conditions of pregnant women. Pregnancy exercise is very important for pregnant women 22 weeks after pregnancy so that it can reduce the incidence of low birth weight and premature birth. The results of the research conducted showed that 100% of pregnant women experienced back pain, although the levels were different and regular pregnancy exercise was proven to reduce back pain. The results of other studies also show that there is an effect of pregnancy exercise on the sleep quality of third-trimester pregnant women. The goal to be achieved through this service activity is to increase the knowledge of pregnant women about pregnancy exercise in the Pemurus Community Health Center Area in the City of Banjarmasin in 2023. The method for this community service activity is a form health promotion and community empowerment programs through counseling and IEC for pregnant women. The results of the community service activities carried out showed an increase in knowledge from before and after counseling by increasing from 45% to 85% being good. The conclusion from this counseling activity is that efforts that can be made to reduce back pain are increasing knowledge through education about pregnancy exercise. Health education or health promotion is carried out from the beginning of pregnancy, it is hoped that this information can change the understanding and knowledge of pregnant women so that pregnant women understand the purpose and indications of pregnancy exercise so that mothers can prepare for pregnancy physiologically.